Preparation method and application of Co / g-C3N4 composite photocatalyst

By loading CoCl2·6H2O onto graphite carbon nitride (g-C3N4), a Co/g-C3N4 composite photocatalyst was prepared, which solved the problem of low efficiency of existing photocatalysts in degrading 2-mercaptobenzothiazole and achieved It achieves efficient photocatalytic degradation effect and low-cost water pollution treatment.

CN115888782BActive Publication Date: 2025-01-21TIANJIN POLYTECHNIC UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111155902.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-30
Publication Date
2025-01-21
Estimated Expiration
2041-09-30

AI Technical Summary

Technical Problem

The existing photocatalyst materials are inefficient in photocatalytic degradation of 2-mercaptobenzothiazole and are costly to achieve effective water pollution treatment.

Method used

By using COCL2 · 6H2O as a cobalt source, it is successfully loaded to graphite nitride (G-C3N4), and the CO/G-C3N4 composite optical catalyst is prepared to use it to improve the photocatalytic activity and the adsorption effect of organic pollutants.

Benefits of technology

The efficient photocatalytic degradation 2-cypogene pyramole is achieved, which significantly improves the removal and degradation efficiency of organic matter in the wastewater, and has good application value and prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115888782B_ABST
    Figure CN115888782B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of composite nanomaterial preparation and environmental protection technology, and discloses a preparation method and application of a Co / g-C3N4 composite photocatalyst. The technology of the present invention synthesizes a composite photocatalyst by a water bath method and a high-temperature calcination method. The preparation process is as follows: first, a certain amount of CoCl2·6H2O and melamine are weighed, deionized water is added, heated and stirred until completely dissolved, and then transferred to a reactor for a water bath reaction, washed and dried after the water bath reaction, and finally the dried sample is calcined to obtain a Co / g-C3N4 composite photocatalyst. The above-mentioned preparation method has a simple preparation process, mild reaction conditions, economical energy saving, and low implementation cost. The prepared composite photocatalyst has both high-efficiency photocatalytic activity and good stability, and has good application value and prospects in the field of photocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photocatalyst material preparation and environmental protection technology, and relates to a preparation method of a Co / g-C3N4 composite photocatalyst and its application in photocatalytic degradation of 2-mercaptobenzothiazole. Background Art

[0002] In recent years, water pollution has become one of the most serious environmental problems. MBT (2-mercaptobenzothiazole) is considered to be a reagent for detecting metals and is used to synthesize pesticides and cephalosporins. Inhalation of low concentrations of MBT can cause nausea and headaches, while inhalation of high concentrations of MBT can cause fatal respiratory paralysis. If it enters the water, it will cause certain harm to the water body. Traditional physical, chemical, and biological methods are difficult to effectively treat such wastewater. The photocatalytic technology developed in recent years not only has strong oxidation ability, fast reaction rate and no pollution, but also has low time and economic costs. It has become one of the important research directions for treating such wastewater. Therefore, the development of new and efficient photocatalysts is one of the best ways to solve this type of water pollution.

[0003] At present, graphite carbon nitride (g-C3N4) is widely studied as an important semiconductor due to its suitable energy band position, easy preparation and good chemical stability. However, its performance is still unsatisfactory due to its insufficient visible light absorption, poor specific surface area, low electronic conductivity and high recombination rate of photogenerated electron-hole pairs. The photocatalytic activity of the material can be improved by enhancing the band structure, light adsorption, charge transport and photoinduced electron-hole pair separation. The photocatalytic activity of g-C3N4 can be effectively improved through various strategies such as synthesis technology, design of nanostructure and regulation of electronic structure.

[0004] Cobalt is often used as an active site for electron transfer and has received increasing attention in photocatalytic applications. When cobalt is loaded on g-C3N4, cobalt as an active site plays a role in electron aggregation, which has a certain effect on improving photocatalytic activity. Therefore, in this patent, CoCl2·6H2O is used as a cobalt source and successfully loaded on g-C3N4. Compared with pure g-C3N4, the photocatalytic activity is significantly improved. Summary of the invention

[0005] [Technical issues]

[0006] In view of the shortcomings of the prior art, an object of the present invention is to provide a method for preparing a Co / g-C3N4 composite photocatalyst, which is simple and easy to implement, has low implementation cost, and the reaction steps are economical and energy-saving.

[0007] Another object of the present invention is to provide a composite photocatalyst prepared by the above-mentioned preparation method, which has both high-efficiency photocatalytic activity and can improve the adsorption effect on organic pollutants, thereby having excellent photocatalytic degradation efficiency, greatly improving the removal and degradation of organic matter in wastewater, and having good application value and prospects in the field of photocatalysis.

[0008] [Technical solution]

[0009] In order to achieve the above object, a method for preparing a composite photocatalyst Co / g-C3N4 is provided according to one embodiment of the present invention.

[0010] (1) Different masses (0.005 g, 0.01 g, 0.02 g, 0.03 g, 0.04 g) of CoCl2·6H2O and 1 g of melamine were weighed into a beaker, 60 mL of deionized water was added, and the mixture was heated in a 90 °C water bath to dissolve. The solution was then transferred into a 100 mL polytetrafluoroethylene-lined reactor and heated at 180 °C for 24 h.

[0011] (2) Cool to room temperature, wash with deionized water and anhydrous ethanol three times respectively, and dry in a vacuum oven at 60°C.

[0012] (3) The powder was placed in a tube furnace and calcined at 550 °C for 4 h at a heating rate of 5 °C / min under N2 atmosphere. The final products were recorded as CoCl2·6H2O according to their mass. 0.005 / g-C3N4,Co 0.01 / g-C3N4,Co 0.02 / g-C3N4,Co 0.03 / g-C3N4,Co 0.04 / g-C3N4. Pure g-C3N4 was prepared without adding CoCl2·6H2O.

[0013] In the step (1), the cobalt salt can be selected from at least one of cobalt nitrate and cobalt chloride, preferably cobalt chloride; the mass of CoCl2·6H2O is 0.001 to 0.1 g, the volume of deionized water is 50 to 100 mL, the water bath dissolution temperature is 50 to 150° C., and the heating time is 16 to 32 h.

[0014] In the step (2), the drying temperature is 50-80°C.

[0015] In the step (3), the calcination temperature is 300-700° C., the calcination time is 2-6 hours, and the heating rate is 2-7° C. / min.

[0016] The Co / g-C3N4 composite catalyst obtained according to the preparation method described above is used to degrade MBT (2-mercaptobenzothiazole) in wastewater.

[0017] The melamine, cobalt chloride hexahydrate (CoCl2·6H2O), and anhydrous ethanol used in the present invention were all analytically pure and purchased from Aladdin Reagent Co., Ltd.

[0018] [Beneficial Effects]

[0019] In summary, the present invention has the following beneficial effects:

[0020] The present invention synthesizes a Co / g-C3N4 composite catalyst, and successfully uses it as a photocatalyst to degrade MBT in wastewater to prepare a tubular catalyst, which can increase its specific surface area, so that reactants are more likely to adhere to the catalyst surface. The Co / g-C3N4 composite catalyst prepared by the present invention is excited by a xenon lamp, contacts with pollutant molecules, and interacts to achieve a special catalytic or conversion effect, so that the surrounding oxygen and water molecules are excited into free negative ions with strong oxidizing power, thereby achieving the purpose of degrading MBT in environmental wastewater. The method does not cause waste of resources and the formation of additional pollution, and is simple to operate and low in cost. It is a green and environmentally friendly and efficient treatment technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 XRD patterns of g-C3N4 and Co / g-C3N4 composite photocatalysts.

[0022] Figure 2 This is the FT-IR image of the Co / g-C3N4 composite photocatalyst.

[0023] Figure 3 For Co 0.01 SEM and TEM images of / g-C3N4 composite photocatalyst.

[0024] Figure 4 For Co 0.01 Absorbance graph and degradation rate graph of MBT degradation by / g-C3N4 composite photocatalyst under visible light.

[0025] Figure 5 Fluorescence spectrum and electrochemical impedance spectroscopy of Co / g-C3N4 composite photocatalyst.

[0026] Figure 6 For Co 0.01 Four-cycle experimental diagram of MBT degradation by / g-C3N4 composite photocatalyst. DETAILED DESCRIPTION

[0027] The present invention will be further described below in conjunction with specific implementation examples.

[0028] The adsorption activity evaluation of the photocatalyst prepared in the present invention was carried out in a CEL-LB70 photochemical reactor, but without turning on the light source, 100 mL of MBT simulated wastewater was added to the reactor and its initial value was measured, and then 0.1 g of photocatalyst was added, the light was not turned on, magnetic stirring was turned on, no ventilation was performed, sampling and analysis were performed every 10 minutes, and the supernatant was taken after centrifugation and entered into the ultraviolet spectrophotometer. Its concentration was measured at λ=310nm, and its adsorption amount Q was calculated by the formula: Q=(C0-C)V / m, where C0 is the initial concentration of the MBT solution, C is the concentration of the MBT solution when the adsorption equilibrium is reached, V is the volume of the solution, and m is the mass of the added catalyst.

[0029] The photocatalytic activity of the photocatalyst prepared in the present invention was evaluated in a CEL-LB70 photochemical reactor (purchased from Beijing Zhongjiao Jinyuan Technology Co., Ltd.) under xenon lamp irradiation. 100 mL of MBT simulated wastewater was added to the reactor and its initial value was determined. Then the prepared photocatalyst was added, magnetic stirring was performed, and the aeration device was turned on to allow air to flow in to keep the catalyst in a suspended or floating state. During the illumination process, sampling and analysis were performed at intervals of 10 minutes. After centrifugation, the upper clear liquid was taken and the absorbance was determined at λmax=310 nm in a spectrophotometer. The degradation efficiency Dr was calculated by the formula: Dr=(C-C0) / C0×100%, where C0 is the concentration after reaching adsorption equilibrium, C is the concentration of the MBT solution measured at time t, and t is the reaction time.

[0030] In order to enable those skilled in the art to more clearly understand the present invention, the present invention is further described in detail below in conjunction with the examples. However, it should be understood that the following examples are only preferred embodiments of the present invention, and the scope of protection claimed by the present invention is not limited thereto.

[0031] <Example>

[0032] Example 1

[0033] The following method is used to prepare the Co / g-C3N4 composite photocatalyst according to the present invention:

[0034] (1) Different masses of CoCl2·6H2O and 1 g of melamine were weighed into a beaker, and 60 mL of deionized water was added. The mixture was heated in a 90 °C water bath to dissolve. The solution was then transferred into a 100 mL polytetrafluoroethylene-lined reactor and heated at 180 °C for 24 h.

[0035] (2) Cool to room temperature, wash with deionized water and anhydrous ethanol three times respectively, and dry in a vacuum oven at 60°C.

[0036] (3) The powder was placed in a tube furnace and calcined at 550 °C for 4 h at a heating rate of 5 °C / min under N2 atmosphere. The final products were recorded as CoCl2·6H2O according to their mass. 0.005 / g-C3N4,Co 0.01 / g-C3N4,Co 0.02 / g-C3N4,Co 0.03 / g-C3N4,Co 0.04 / g-C3N4.

[0037] Example 2

[0038] The same steps as in Example 1 were followed, except that 0.005 g of CoCl2·6H2O was weighed in (1), and Co 0.005 / g-C3N4 was subjected to a photocatalytic degradation test in a photochemical reactor, and it was found that the degradation efficiency of the photocatalyst for MBT solution reached 93% within 70 minutes.

[0039] Example 3

[0040] The same steps as in Example 1 were followed, except that 0.01 g of CoCl2·6H2O was weighed in (1), and Co 0.01 / g-C3N4 was subjected to a photocatalytic degradation test in a photochemical reactor, and it was found that the degradation efficiency of the photocatalyst for MBT solution reached 98% within 70 minutes.

[0041] Example 4

[0042] The same steps as in Example 1 were followed, except that 0.02 g of CoCl2·6H2O was weighed in (1), and Co 0.02 / g-C3N4 was subjected to a photocatalytic degradation test in a photochemical reactor, and it was found that the degradation efficiency of the photocatalyst for MBT solution reached 91% within 70 minutes.

[0043] Example 5

[0044] The same steps as in Example 1 were followed, except that 0.03 g of CoCl2·6H2O was weighed in (1), and Co 0.03 The photocatalytic degradation test of / g-C3N4 in a photochemical reactor was carried out, and the degradation efficiency of the photocatalyst on MBT solution was measured to reach 83% within 70 minutes.

[0045] Example 6

[0046] The same steps as in Example 1 were followed, except that 0.04 g CoCl2·6H2O was weighed in (1), and Co 0.04 / g-C3N4 was subjected to a photocatalytic degradation test in a photochemical reactor, and it was found that the degradation efficiency of the photocatalyst for MBT solution reached 80% within 70 minutes.

[0047] from Figure 1 (a) The XRD of the prepared composite photocatalyst Co / g-C3N4 shows obvious absorption peaks at 13.1° and 27.3°, corresponding to the (100) and (002) crystal planes of g-C3N4, respectively. The absorption peak at 27.3° is more obvious, which is due to the stacking diffraction of the interlayer spacing of the (002) lattice plane of the graphite-like structure. As the loading amount of Co increases, the diffraction peak at 27.3° gradually becomes wider, indicating that there is a strong attraction between Co and g-C3N4. It can be seen from the observation that the diffraction peak of g-C3N4 has no offset, indicating that the Co element is only loaded on the surface of g-C3N4 and has not entered the crystal structure. In addition, no other characteristic impurity peaks were detected in these samples, indicating that they are pure phases with the same crystal structure. Since from Figure 1 The form of Co cannot be known in (a). The reason for this may be that the amount of CoCl2·6H2O added is too small. Therefore, the amount of CoCl2·6H2O is increased to 0.5g of cobalt source, thus obtaining Figure 1 (b) It can be seen that in addition to the diffraction peak at 27.3°, there are three diffraction peaks at 45.9°, 53.5°, and 79.1°. According to the XRD standard card Co PDF-88-2325, these three diffraction peaks belong to Co element. Therefore, the Co / g-C3N4 composite photocatalyst was successfully prepared.

[0048] from Figure 2 The FT-IR spectra of all samples showed a peak at 810 cm -1 There is a characteristic peak, belonging to the breathing vibration of the triazine unit, at 1200-1700cm -1 There are several peaks in between, which are typical stretching vibrations of CN heterocycles, 3100cm -1 The nearby region belongs to the stretching vibration of NH. Therefore, the preparation of Co / g-C3N4 composite photocatalyst is successful.

[0049] from Figure 3 The SEM image in (a) shows that the composite material Co 0.01 / g-C3N4 is a hollow tubular structure with smooth surface, and some Co particles of different sizes are scattered on the surface. Figure 3 The TEM image (b) further shows that the Co particles are attached to g-C3N4, indicating that the Co / g-C3N4 photocatalytic material is successfully composited.

[0050] Figure 4 (a) Composite photocatalyst Co under visible light 0.01 / g-C3N4 degraded MBT solution absorbance diagram. It can be seen that with the increase of time, the characteristic peak at 310nm corresponding to MBT gradually weakened, indicating that the MBT molecules were significantly degraded and destroyed. Figure 4 (b) shows more intuitively the degradation efficiency of the six catalysts under the same conditions. 0.01 / g-C3N4 has the best degradation effect, and blank experiments have proved that the influence of photosensitization on MBT is excluded.

[0051] pass Figure 5 (a) It can be seen that compared with the single g-C3N4 catalyst, Co 0.01 The fluorescence intensity of the / g-C3N4 composite photocatalyst is low, indicating that the recombination rate of photogenerated carriers in the composite photocatalyst is low, thus improving the photocatalytic activity. Figure 5 As can be seen from (b), compared with the single g-C3N4 catalyst, Co 0.01 The radius of the / g-C3N4 composite photocatalyst is smaller, indicating that this composite photocatalyst has better interfacial charge transfer characteristics and is more conducive to the separation and migration of carriers, thereby improving the photocatalytic performance.

[0052] pass Figure 6 It can be seen that after four photocatalytic experiments, Co 0.01 The / g-C3N4 composite photocatalyst showed relative stability in the degradation of tetracycline under visible light, with a slight decrease in the last two times, mainly because after each experiment, there was a certain loss of the sample during the washing and drying process.

Claims

1. Application of a Co / g-C3N4 composite photocatalyst in the efficient removal of 2-mercaptobenzothiazole MBT in the environment, characterized in that: The preparation method of the composite photocatalyst comprises the following steps: (1) Weigh different masses of CoCl2·6H2O (0.005 g, 0.01 g, 0.02 g, 0.03 g, and 0.04 g) and melamine into a beaker, add deionized water, heat in a water bath to dissolve, and then transfer the solution into a 100 mL polytetrafluoroethylene-lined reactor for hydrothermal reaction; (2) Cool to room temperature, wash with deionized water and anhydrous ethanol three times respectively, and then dry; (3) The powder is placed in a tubular furnace and calcined under a N2 atmosphere to obtain the Co / g-C3N4 composite photocatalyst.

2. The use according to claim 1, characterized in that: In the step (1), the volume of the deionized water is 50 to 100 mL.

3. The use according to claim 1, characterized in that: In the step (1), the dissolving temperature is 80-100°C by heating in a water bath.

4. The use according to claim 1, characterized in that: The step (1) further comprises: the hydrothermal reaction temperature is 150 to 220° C., and the reaction time is 20 to 28 hours.

5. The use according to claim 1, characterized in that: In the step (2), the drying temperature is 50-80°C.

6. The use according to claim 1, characterized in that: In the step (3), the calcination temperature is 450-650° C., the calcination time is 3-6 hours, and the heating rate is 5-10° C. / min.

Citation Information

Patent Citations

  • Co / V double-metal-doped g-C3N4 photocatalyst and preparation method and application thereof

    CN112007679A